2003
DOI: 10.1097/00005131-200307000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Unstable Pelvic Fractures Fixed with Percutaneous Iliosacral Screws: Does Posterior Injury Pattern Predict Fixation Failure?

Abstract: Percutaneous iliosacral screw fixation is a useful technique in the management of vertically unstable pelvic fractures, but a vertical sacral fracture should make the surgeon more wary of fixation failure and loss of reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
123
0
13

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(137 citation statements)
references
References 16 publications
1
123
0
13
Order By: Relevance
“…Zhao et al showed that TSTI provides superior biomechanical fixation than IS screws in finite element analysis and cadaveric models [18,19]. This type of fixation has been proposed as a solution to previous failures of IS screws with vertically unstable sacral fractures according to Griffin et al [4]. A few small retrospective studies have shown good clinical results with TSTI screws [1,3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhao et al showed that TSTI provides superior biomechanical fixation than IS screws in finite element analysis and cadaveric models [18,19]. This type of fixation has been proposed as a solution to previous failures of IS screws with vertically unstable sacral fractures according to Griffin et al [4]. A few small retrospective studies have shown good clinical results with TSTI screws [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…TSTI screws were generally more likely to be used in patients with vertically unstable injuries of the posterior ring as a result of previous reports of failures [4] or in osteopenic patients; however, the decision to use IS or TSTI fixation was made according to the judgment of the attending traumatologist. The techniques used were described in the technique paper by Gardner and Routt [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Griffin et al [4] have shown that the use of percutaneous iliosacral screw fixation may be a good technique to manage vertically unstable sacral fractures, but there are some anatomic limitations, and in order to prevent fixation failure prolonged bed rest is often necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Operative treatment should reconstruct the fracture anatomy, decompress the nerves, and achieve possibly early mobilization and weight-bearing. Kinds of internal fixation instruments that had been proposed to reconstruct the post pelvic ring include posterior small plates [5], percutaneous iliosacral screws [6,7], transiliac bars [8][9][10], and sacral rods [11]. However, none of these fixation instruments can resist vertical shear forces, provide unrestricted weightbearing, and secure mobilization after operation.…”
Section: Introductionmentioning
confidence: 99%